An overview of structural designs and building materials in shell structure for the mosque and the future development. (April 2020) - Nugrahini, F C
Abstract: The developments of technology in realizing contemporary designs become a hot issue for the development of the mosque's appearance and shape. The development of the shell building in the mosque which is quite attractive to the public was the construction of the Cologne Central Mosque in Germany in 2017. For the point of view that shape of the building is a new era in the use of shell structures in the mosque. The shell structure commonly used as a dome of the mosque that is used as a symbol of the mosque buildings in general use and continues to this day which began from the era of the caliphate. This paper will present a review of the structural designs and building materials on the shell structure of the mosque which has been developing from time to time. And can be used as a possible new reference in the future developments of mosque architecture.